Influence Independent Teaching Platform (PMM) and Work Motivation for Implementation Independent Curriculum at SMP Negeri 1 Sindue - Karim, Moh.; Misnah, Misnah; Hasdin (Journal of Education Method and Learning Strategy, 2025)
This study aims to 1). determine the Influence of the Merdeka Mengajar Platform (PMM) on the Implementation of the Merdeka Curriculum at SMP Negeri 1 Sindue, 2). to determine the Influence of Work Motivation on the Implementation of the Merdeka Curriculum at SMP Negeri 1 Sindue, 3). to determine the Influence of the Merdeka Mengajar Platform (PMM) and Work Motivation on the Implementation of the Merdeka Curriculum at SMP Negeri 1 Sindue. This type of research is quantitative research with a survey approach. The number of populations and samples is the same, namely, 27 teachers using the technique of taking samples, which is total sampling or saturated sampling. Data collection will use questionnaires, interviews, and documentation to test hypotheses using the formula multiple linear regression. The results show that 1). The influence of the independent teaching platform (PMM) on the implementation of the independent curriculum at SMP Negeri 1 Sindue has a significance value of 0.015 and a contribution value of B of 0.546. 2). Work motivation has an influence on the implementation of the independent curriculum at SMP Negeri 1 Sindue, with a significance value of 0.044 and a contribution value of B of 0.414. 3). There is an Influence of the Independent Teaching Platform (PMM) and Work Motivation on the Implementation of the Independent Curriculum at SMP Negeri 1 Sindue, which has a very high significance level of 0.000 with a contribution level of influence or R² of 0.835 (83.5%) and an F value of amounting to 60,545 and there are around 16.5% of other factors or variables that influence the existing variables.